1997
DOI: 10.2139/ssrn.15071
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Complex Bioeconomic Simulations Using an Efficient Search Heuristic

Abstract: For simulation to be truly useful for investigating many problems in agricultural economics, nonsimplifying optimization techniques need to be employed. General methods for simulation optimization that do not inhibit system characterization or analysis are available, and they would appear to provide much of the mathematical and optimizing rigor demanded by economists. This paper describes the theory and algorithm of a robust and efficient simulation optimization approach, the Complex Method. An example of impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…The complex method is another efficient optimization algorithm searching from the initial simplexes for the optimization of either physical processes or mathematical functions [17]. Even though the complex method is a direct method, it does not require the gradients of the objective function for searching.…”
Section: Application Of Pso-complex Hybridmentioning
confidence: 99%
See 2 more Smart Citations
“…The complex method is another efficient optimization algorithm searching from the initial simplexes for the optimization of either physical processes or mathematical functions [17]. Even though the complex method is a direct method, it does not require the gradients of the objective function for searching.…”
Section: Application Of Pso-complex Hybridmentioning
confidence: 99%
“…The need to improve the simplex method and become the complex method is presented in [17]. With the concavity of nonlinear functions, the simplex method may be directed to a less feasible solution space during the reflection and expansion operations.…”
Section: Application Of Pso-complex Hybridmentioning
confidence: 99%
See 1 more Smart Citation
“…Umeda, Shindo and Ichikawa (1972) used this method to solve variational problems with state-variable inequality constraints and demonstrated its applicability. Kazmierczak (1996) gave an example of a pest management problem to illustrate that the Complex Method was a very efficient optimization approach and mathematically very simple 10 compared to some other methods. Erdogdu and Balaban (2002) modified this method and showed that it allowed the incorporation of different constraints on microbial sterility and final temperature at the coldest point as implicit constraints in thermal processing problems.…”
Section: Optimization Algorithmmentioning
confidence: 99%
“…These problems are especially difficult to solve because of the non-linear and distributed nature of the system dynamics and the existence of explicit and implicit constraints on both control variable and objective function (Banga et al, 2001). There have been numerous methods suggested for this kind of problem and accumulated knowledge in the literature (Gallardo & Casares, 1991;Noronha, Hendrickx, Suys, & Tobback, 1993;Banga & Seider, 1996;Kazmierczak, 1996;Noronha, Loey, Hendrickx, & Tobback, 1996a,b;Terajima & Nonaka, 1996;Banga, Perez-Martin, Banga, Alonso & Singh, 1997;Chalabi, Van Willigenburg, & Van Straten, 1999;Banga et al, 2001;Balsa-Canto, Alonso & Banga, 2002;Erdogdu & Balaban, 2002). As seen in the literature, the maximum principle of Pontryagin has been used by many authors to solve the thermal processing optimization problems.…”
Section: Introductionmentioning
confidence: 99%